MANAJEMEN PESERTA DIDIK DALAM MENGEMBANGKAN MULTIPLE INTELLIGENCES DAN PRESTASI NONAKADEMIK SISWA MADRASAH TSANAWIYAH - Tsania Alfiaturrohmah; Muhlil Musolin; Rosyidah Nur Lailiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student management plays an important role in developing multiple intelligences and non-academic achievements of Madrasah Tsanawiyah students; however, it has not been fully optimized. This study aims to analyze the implementation of student management in developing students’ multiple intelligences and non-academic achievements. The study employed a qualitative approach with a case study design at MTs N 1 Purworejo. The subjects were the headmaster, vice principals, teachers, extracurricular coaches, and students. Data were collected through interviews, observations, and document studies, and analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results showed that student management in developing multiple intelligences and non-academic achievements was carried out systematically through planning (new student admission, potential identification, class grouping), implementation (learning and extracurricular activities based on multiple intelligences), and periodic academic and non-academic evaluation. It is concluded that structured and collaborative student management can optimize the development of multiple intelligences and non-academic achievements. The implication is that madrasahs need to strengthen technology-based potential assessment and continuous evaluation as an effort to improve quality.